Role of procurement and supply chain management in construction project performance: a case on Pakiza Industrial Park - Das, Tushar Kanti (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.